Managing an invasive tree in coastal dunes: The importance of follow-up treatments to improve the recovery of protected habitats - Duarte, Liliana Neto; Marchante, Elizabete; Marchante, Hélia (Frontiers in Environmental Science, 2023)
Conservation of biodiversity in protected areas is often threatened by invasive alien plants (IAPs), and its successful management requires proper planning, resources, and monitoring to adjust future interventions. Although follow-up controls and evaluation of different management actions through monitoring programs are crucial in an adaptive management strategy, they are often neglected. Acacia longifolia is one of the most widespread IAPs in the Portuguese coastal areas, causing several negative impacts. This study reports the results of different control methods of A. longifolia in two forest plantations over coastal dunes in two protected sites in Portugal, under different management regimes and for over 4 years. The best results were achieved after hand pulling, but due to its high cost, this method is not suitable for large areas. Mechanical cuts, which include the use of brush hogs, brush cutters, and chainsaws, resulted in variable levels of resprouting of A. longifolia stumps. Follow-up treatments, whether mechanical and/or chemical, reduced the number of A. longifolia resprouts and kept its cover below 20% and height below 50 cm. Furthermore, controlling with brush cutters/hogs reduced the seed bank of A. longifolia by 74% while that with a disc harrow allowed an even greater reduction (91%). In areas where no follow-up treatments were carried out, A. longifolia started producing flowers two and a half years after the initial treatment, restarting the cycle of seed production. Nevertheless, a biological control agent that reduces A. longifolia seed production (Trichilogaster acaciaelongifoliae) establishment was confirmed in the controlled areas, suggesting that new seed production by these plants will be soon controlled. Although species characteristic of the protected habitats are currently poorly represented, it is expected that they begin to emerge with the reduction of A. longifolia. Our results stress the importance of persistence of follow-up treatments if higher success in IAPs control is to be achieved, not only because of the resprouting ability of many species (despite this not being very common in A. longifolia) but also because invasive plants can produce extensive persistent seed banks. The role of the management regime on the level of success in controlling IAPs will be discussed.